Utilizing cost-effective pyrocarbon for highly efficient gold retrieval from e-waste leachate - Fu, Kaixing; Liu, Xia; Zhang, Xiaolin; Zhou, Shiqing; Zhu, Nanwen; Pei, Yong; Luo, Jinming (Nature communications, 2024)
Addressing burdens of electronic waste (E-waste) leachate while achieving sustainable and selective recovery of noble metals, such as gold, is highly demanded due to its limited supply and escalating prices. Here we demonstrate an environmentally-benign and practical approach for gold recovery from E-waste leachate using alginate-derived pyrocarbon sorbent. The sorbent demonstrates potent gold recovery performance compared to most previously reported advanced sorbents, showcasing high recovery capacity of 2829.7 mg g −1 , high efficiency (>99.5%), remarkable selectivity ( K d ~ 3.1 × 10 8 mL g −1 ), and robust anti-interference capabilities within environmentally relevant contexts. The aromatic structures of pyrocarbon serve as crucial electrons sources, enabling a hydroxylation process that simultaneously generates electrons and phenolic hydroxyls for the reduction of gold ions. Our investigations further uncover a “stepwise” nucleation mechanism, in which gold ions are reduced as intermediate gold-chlorine clusters, facilitating rapid reduction process by lowering energy barriers from 1.08 to −21.84 eV. Technoeconomic analysis demonstrates its economic viability with an input-output ratio as high as 1370%. Our protocol obviates the necessity for organic reagents whilst obtaining 23.96 karats gold product from real-world central processing units (CPUs) leachates. This work introduces a green sorption technique for gold recovery, emphasizing its role in promoting a circular economy and environmental sustainability. The demand for gold recovery from E-Waste is significant due to its high value. Here, authors present a practical method for extracting gold from an actual E-waste leachate using alginate-derived pyrocarbon. This approach yields a 23.96 karat gold product and demonstrates strong economic viability.